A web platform and a decision model for computer-interpretable guidelines - Oliveira, T. (2013)
Situations of medical error and defensive medicine are com- mon in healthcare environments and have repercussions in the quality of care under o er. The occurrence of adverse events and the increase of healthcare expenses are some of the consequences of medical malpractice. Indeed, these situations may be prevented by encouraging the compli- ance with Clinical Guidelines (CGs). However, the current format of CGs proved to be disadvantageous for real-time application, i.e., they may not provide recommendations to healthcare professionals when required, and on time. The introduction of Computer-Interpretable Guidelines (CIGs) may provide a solution to this problem, however they are not widely implemented and there are some issues that need to be contemplated. Indeed, in this paper it is presented the CompGuide project for guideline representation and sharing, combined with the handling of incomplete information in that context.